Numerical experimentation to develop design and operational parameters for skimming wells: a case study of the Chaj Doab of Punjab, Pakistan - Aslam, Muhammad (2015)
In the present study, MODFLOW-MT3D groundwater model was employed to perform numerical experimentation to develop design and operational parameters for skimming wells based on hydrogeology and groundwater salinity conditions of Chaj Doab, Punjab, Pakistan. Numerical experimentation resulted in: (i) a 1-strainer SW (Skimming Wells) with discharge of 14 l/s (litres per second) and penetration of 30% resulted in more saltwater upconing at 8 hours/day well operation compared to that occurred at 4 hours/day operation; (ii) a 1-strainer well with penetration of 30% and operation of 8 hours/day caused higher saltwater upconing at 14 l/s discharge compared to that at 9 l/s discharge; (iii) a 4-strainer well with penetration of 30% and operation of 8 hours/day also caused more saltwater upconing at 14 l/s well discharge compared to that at 9 l/s discharge. Similar trend was found for a 8-strainer well; and (iv) 1- or 4- or 8-strainer well with 30-60% penetration, 9-14 l/s discharge and 4-8 hours/day operation could provide pumped groundwater of salinity less than 1000 ppm. Considering hydro-chemical performance and costs of wells, a 4-strainer well with 30% penetration, 9-14 l/s discharge and 4-8 hours/day operation is recommended to skim groundwater of salinity less than 1000 ppm in Chaj Doab of Punjab, Pakistan.